INTEGRATING ISLAMIC PERSPECTIVES INTO MENTAL HEALTH SERVICES FOR OLDER ADULTS: PROSPECTS AND CHALLENGES - Hoque, Mesbahul; Azmi, Ahmad Sanusi; Abdul Rahman, Mohd Zahir; Zulkiply , Shah Rizul Izyan; Toure, Abdoul Karim (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
As the global population ages, mental health challenges among older adults are becoming increasingly prevalent. Many elderly individuals experience issues such as loneliness, depression, anxiety, and cognitive decline, which can significantly affect their overall well-being. In this context, religion—particularly Islam—offers valuable resources for emotional and psychological support. This article explores the importance of integrating Islamic perspectives into mental health services, suggesting that incorporating spiritual values can enhance the effectiveness and acceptance of mental health interventions among Muslim elderly. Finally, the article addresses key barriers to providing effective Islamic mental health services, such as stigma, lack of culturally trained professionals, and limited awareness within both healthcare and religious communities. By reviewing relevant literature and drawing on religious sources, this study highlights the potential of Islam to serve as a supportive framework for improving mental health outcomes in later life. The findings suggest that mental health strategies that align with Islamic values can help create more inclusive and compassionate care for the aging Muslim population, while also addressing systemic gaps in current mental health service delivery.